TINDAK PIDANA KORUPSI PENYALAHGUNAAN WEWENANG - MUHAMAD DLUHA (STIH Zainul Hasan Kraksaan Kraksaan, 2022)
Abstract Corruption crime has a very broad scope into 7 types, namely state financial losses, bribery, bribery, abuse of office/authority, extortion, fraudulent acts, conflicts of interest and gratuities. Corruption is an extraordinary crime, so the threat of criminal sanctions is very heavy. The problems studied in this study and their objectives can be formulated firstly to determine the provisions on abuse of authority in corruption crimes regulated in Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Corruption Crimes (UUPTPK) and secondly to find out criminal sanctions against perpetrators of corruption in the abuse of authority in the UUPTPK mentioned above. Based on the formulation of the problem and research objectives, the method used in this research is normative juridical, namely by reviewing legislation, legal theories related to the problems discussed and based on their nature using descriptive analytical methods is research that clearly describes and pay close attention to the matters in question. The results of the research in this thesis, firstly, the provisions on abuse of authority in criminal acts of corruption are clearly regulated in Article 3 of Law Number 31 of 1999 jo. Law Number 20 of 2001 concerning Eradication of Criminal Acts of Corruption (UUPTPK) and the two criminal sanctions against perpetrators of corruption in abuse of authority are life imprisonment or imprisonment for a minimum of 1 (one) year and a maximum of 20 (twenty) years and or a minimum fine of Rp. 50,000,000 (Fifty Million Rupiah) and a maximum of Rp. 1,000,000,000.00 (One Billion Rupiah).